Improved Location And Positioning Utilizing Single MIMO Base Station In IMT-Advanced System - Azmi, Awang Md Isa; Mustafa H., Othman; Zahariah, Manap; Mohd Sa'ari, Mohamad Isa; Mohd Shahril Izuan, Mohd Zin; Mohd Shakir, Md Saat; Zahriladha, Zakaria (Penerbit Universiti, UTeM, 2016)
This paper discusses an improvement of location and positioning estimation using one of the IMT-Advanced systems known as the mobile WiMAX. The Single MIMO Base Station (SMBS) in mobile WiMAX is combined with a virtual technique, known as the Virtual Base Stations, created a novel algorithm for location and positioning (L&P) purposes. This algorithm based on the angle of arrival (AOA) and angle of departure (AOD) measurement parameter completed the new SMBS algorithm with virtual base station (SMVirBS). The developed algorithm includes the effect of the geometric dilution of precision (GDOP) to assist with the location estimation accuracy. The simulation results showed that the proposed SMVirBS technique always outperforms the linear least square (LLS) algorithm in terms of estimated location accuracy. The technique also has the capability to work well in non-line of sight errors (NLOS).